2010
DOI: 10.1097/aln.0b013e3181ca7a9b
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Pulse Oximetry Surveillance on Rescue Events and Intensive Care Unit Transfers

Abstract: Background: Some preventable deaths in hospitalized patients are due to unrecognized deterioration. There are no publications of studies that have instituted routine patient monitoring postoperatively and analyzed impact on patient outcomes. Methods: The authors implemented a patient surveillance system based on pulse oximetry with nursing notification of violation of alarm limits via wireless pager. Data were collected for 11 months before and 10 months after implementation of the system. Concurrently, matchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
199
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(207 citation statements)
references
References 15 publications
(9 reference statements)
3
199
0
5
Order By: Relevance
“…Strictly examining the alarms within the scope of the study, the alarm frequency distribution resembles that of Stepdown units, with high respiratory rate, high heart rate, and low SpO 2 being the most common alarms. These alarm frequency distributions confirm existing studies that identify parameter alarms for heart rate and SpO 2 as being prone to nuisance alarms, along with the couplet arrhythmia alarm [7,11]. However, respiratory rate alarms have not been specifically identified in previously published literature, and, based on their prevalence in both the Stepdown unit and ICU distributions, merit further investigation as to their default settings.…”
Section: Alarm Frequency Distribution For Stepdown Unitssupporting
confidence: 58%
See 3 more Smart Citations
“…Strictly examining the alarms within the scope of the study, the alarm frequency distribution resembles that of Stepdown units, with high respiratory rate, high heart rate, and low SpO 2 being the most common alarms. These alarm frequency distributions confirm existing studies that identify parameter alarms for heart rate and SpO 2 as being prone to nuisance alarms, along with the couplet arrhythmia alarm [7,11]. However, respiratory rate alarms have not been specifically identified in previously published literature, and, based on their prevalence in both the Stepdown unit and ICU distributions, merit further investigation as to their default settings.…”
Section: Alarm Frequency Distribution For Stepdown Unitssupporting
confidence: 58%
“…A study from Taenzer et al discussed the connection of alarm fatigue to the total number of rescue events [7]. These do not necessarily result to patient loss, but do account for increased care costs due to patients being transferred to higher acuity levels, increased length of stay, or other complications associated with the patient's deteriorated condition.…”
Section: Patient Monitoring and Alarm Fatiguementioning
confidence: 99%
See 2 more Smart Citations
“…9,11,12 Continuous monitoring using pulse oximetry with nurse notification of violation limits via wireless pager in postoperative patients found a reduction in ICU transfers of 25% to 50% and rapid response team activations of 45% to 60% on surgical floors, resulting in a reduction of ICU days by 135 in a 1-year period. 13 Additionally, a recent study showed that reintubation in patients with OSA occurred earlier in the postoperative course and had a better prognosis than in patients without OSA. 9 This suggests that many occurrences of respiratory failure in OSA patients may be related to transient respiratory compromise which can be managed successfully with early detection.…”
Section: Discussionmentioning
confidence: 99%